I Want to Die Well. Issue 2 (March 2023) - Johnson, Amber
Public health scholars, practitioners, organizations, and governmental agencies broadly declared that racism is a public health crisis in 2020. Their declarations highlight the need to address how racism destroys Black life and communities. This poem looks at the various ways Black people have died in the United States due to racism, and offers a comparison to wealthy white men whom often die peacefully, of old age, surrounded by money and generations of family. This poem is but a glimpse into the many ways Black life ends painfully at the hands of racist systems, policies, and people—an unfiltered reminder of the imperative of committing to antiracist praxis within health promotion research and practice. To view the original version of this poem, see the supplemental material section of this article online.